Działalność fundacyjna Kazimierza Sprawiedliwego w świetle nowych badań - Sikora, Jerzy (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
In 1995 a Ph.D. dissertation of a historian from Poznań – Józef Dobosz (Działalność fundacyjna Kazimierza Sprawiedliwego, Poznań 1995) was published. The author reviewed scanty written sources and surveyed archaeological and architectural researches in order to lully reconstruct the foundational activity of the prince as well as the circle of magnates who cooperated with him. The above article is a kind of a comment on this work written from an archaeologist's point of view. Casimir II (since 1166 the prince of Wiślica, and since 1177 sovereign of the whole Little Poland, at the end of his life he also ruled the Łęczyca Land, the eastern Little Poland and Mazovia; died during an expedition to Prussia in 1194) pursuing his foundational activity he closely cooperated with clergymen and secular magnates who were gathered around him, including such personalities of the 12,b century as archbishop of Gniezno Piotr, bishop of Kraków Gcdko, Jaksa from Miechów, comes Radosław or knight Bałdrzych. Casimir’s activity in many cases was a continuation of his older brother’s Henry of Sandomierz foundational activity (after whom he came to power). The area of that activity was basically limited to the Little Poland region. On the grounds of analysis of historical sources and field investigations the mentioned circle of people can be connected with foundation of many objects that have been preserved to a different degree and submitted to (also to a different degree) archaeological and architectonic investigations. First of all, enlarged residential complex in Wiślica (site Regia), consisting of two arrangements of oblong buildings of palatio type that were connected on an axis with central chapels. Their distant analogies were found in imperial pfaltzs in Paderborn and Goslar. It can be presumed that Henry of Sandomierz started the building of the complex. In Wiślica also should be mentioned relics of the Romanesque collegiate church (so-called church I revealed under the floor of the present Gothic building) together with beautiful engraved gypsum floor in the crypt of the building. With Casimir's activity other foundations of collegiate churches are also connected – in Sandomierz, Opatów and St. Florian, on Kleparz in Kraków (their architectural shape, except the church in Opatów, is unknown). A. Tomaszewski suggested that it is possible that it was Casimir who constructed St. Nicolas church in Żarnowo, mentioned in a document from 1191 presenting properties of the collegiate church in Sandomierz. This assumption should be sustained at the present state of knowledge. Simultaneously, there is a possibility of connecting the following churches mentioned in the document with the prince - one of unknown architectonic shape in Świeże and tetraconchos of St. Maurice in Zawichost, revealed as a result of archaeological excavations in 1994, 1996-1999, with many analogies in 12th century architecture in Czech and Moravia. Also a group of Cistercian monasteries in Little Poland from the 12th century in Jedrzejów, Sulejów, Koprzywnica and Wąchock attracts attention. Apart from disputably dated relics of a sacral building in Jedrzejów (so-called church I) and unclear results of investigations in Wąchock, the 12th century shape of these buildings is still unknown. Probably in the 12th century only wooden buildings were constructed which in the next century started to be replaced by classical, „Bernardine” basilicas and by gradually built claustrum buildings. The review of the foundational activity of the prince and his court are completed by church of commandery of the knights of St. John of Jerusalem in Zagość (unique because of rich, „Lombardian” archilectonical decoration) and by still unrecognised the Knights of the Holy Sepulchre in Miechów as well as an adaptation of St. Salvatore church in Zwierzyniec in Kraków into monastic Premonstratensian church (so-called 3rd church) and mysterious Romanesque wall elements in the area of the present monastery in Zwierzyniec. The review is ended by also unrecognised branch of this monastery in Skowieszynek near Kazimierz Dolny. Worth being noticed is special meaning of canonical foundations (collegiate churches) which, as a rule, got a rich architectonical programme contrary to monastic churches, where rather temporary wooden buildings which only during functioning of the convent (most often only in the next century) were gradually replaced by masonry ones in the late-Romanesque style. An attention has also been drawn to, not entirely clear, but probably great, role of Casimir’s wife, the princess of Znojmo Helen in the foundational activity of the prince.